2018
DOI: 10.1177/1479164118802759
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of effects of sodium-glucose co-transporter 2 inhibitor in Japanese type 2 diabetes mellitus patients with chronic kidney disease

Abstract: Aim: The aim of this study was to assess the renal effects of the glucose-lowering SGLT2 inhibitors in Japanese type 2 diabetes mellitus patients with chronic kidney disease. Methods: The Kanagawa Physicians Association maintains a registry of patients who visit their 31 clinics. Clinical data of type 2 diabetes mellitus patients with chronic kidney disease, who were prescribed SGLT2 inhibitors in addition to other treatments, were collected and analysed. Results: SGLT2i was associated with a fall in HbA 1c fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Compared to baseline, the proportion of patients with microalbuminuria decreased by 5.9% with SGLT2 inhibition. In another similar study by Kobayashi et al using the Kanagawa Physicians Association registry, 786 T2D participants with CKD treated with SGLT2 inhibition for a median period of 13 months demonstrated a significant decline in median UACR from 47.1 mg/g creatinine to 41.1 mg/g creatinine . Finally, DARWIN‐T2D was a large real‐world retrospective study conducted in 46 Italian outpatient clinics .…”
Section: Kidney Protection In Cvotsmentioning
confidence: 95%
“…Compared to baseline, the proportion of patients with microalbuminuria decreased by 5.9% with SGLT2 inhibition. In another similar study by Kobayashi et al using the Kanagawa Physicians Association registry, 786 T2D participants with CKD treated with SGLT2 inhibition for a median period of 13 months demonstrated a significant decline in median UACR from 47.1 mg/g creatinine to 41.1 mg/g creatinine . Finally, DARWIN‐T2D was a large real‐world retrospective study conducted in 46 Italian outpatient clinics .…”
Section: Kidney Protection In Cvotsmentioning
confidence: 95%
“…In our previous study, we confirmed the beneficial renal effects of SGLT2 inhibitors in Japanese patients with type 2 DM and CKD. 5,6 In a Japanese prospective study, dapagliflozin significantly improved albuminuria levels and the home BP profile in T2DM and diabetic nephropathy patients, and the improved morning home systolic BP was associated with an albuminuria reduction. 7 From these studies, SGLT2Is are thought to be suitable for the treatment of diabetic patients with CKD.…”
mentioning
confidence: 99%
“…We reported recently the renoprotective effect of SGLT2i in Japanese T2DM patients with CKD [3]. The multiregression analysis applied in that study demonstrated the importance of a decrease in BP as an independent factor for the improvement of ACR.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several large-scale cardiovascular outcome clinical trials on SGLT2i, such as the EMPA-REG OUTCOME trial [1] and CANVAS/CANVAS-R program [2], showed significant improvement in cardiovascular events and even diabetic nephropathy in T2DM patients. Our group also reported previously that SGLT2i reduce the urinary albumin-creatinine ratio (ACR; mg/gCr) in Japanese T2DM patients with chronic kidney disease (CKD) [3]. This mechanism of this effect was not completely understood and presumed to be indirectly related to a decrease in BP.…”
Section: Introductionmentioning
confidence: 98%